Meningococcal Disease in Patients With Human Immunodeficiency Virus Infection: A Review of Cases Reported Through Active Surveillance in the United States, 2000–2008. (20th December 2016) - Harris, Christine M.; Wu, Henry M.; Li, Jianmin; Hall, H. Irene; Lee, Adria; Zell, Elizabeth; Harrison, Lee H.; Petit, Susan; Farley, Monica M.; Lynfield, Ruth; Miller, Lisa; Nichols, Megin; et al.
Abstract: Background: Although human immunodeficiency virus (HIV) infection is an established risk factor for several bacterial infections, the association between HIV infection and meningococcal disease remains unclear. Methods: Expanded chart reviews were completed on persons with meningococcal disease and HIV infection reported from 2000 through 2008 from 9 US sites participating in an active population-based surveillance system for meningococcal disease. The incidence of meningococcal disease among patients meeting Centers for Disease Control and Prevention acquired immune deficiency syndrome (AIDS) surveillance criteria was estimated using data from the National HIV Surveillance System for the participating sites. Results: Thirty-three cases of meningococcal disease in individuals with HIV infection were reported from participating sites, representing 2.0% of all reported meningococcal disease cases. Most (75.8%) persons with HIV infection were adult males aged 25 to 64 years old. Among all meningococcal disease cases aged 25 to 64 years old, case fatality ratios were similar among HIV-infected and HIV-uninfected persons (13.3% vs 10.6%; P = .6). The cumulative, mean incidence of meningococcal disease among patients aged 25 to 64 years old with HIV infection ever classified as AIDS was 3.5 cases per 100000 person years (95% confidence interval [CI], 2.1–5.6), compared with 0.3 cases per 100000 person years (95% CI, 0.3–0.3) for persons of the same age group not reported to have AIDS (relative risk = 12.9; 95% CI, 7.9–20.9). Conclusions: Individuals with HIV infection meeting the AIDS surveillance case definition have a higher incidence of meningococcal disease compared with the general adult population.